Evaluasi Indeks Kepuasan Masyarakat (IKM) Periset terhadap layanan Perpustakaan Badan Riset dan Inovasi Nasional Tahun 2022 - Wulandari, Suci; Tupan, Tupan; Maha, Rahmadani Ningsih (Daluang: Journal of Library and Information Science, 2023)
Introduction. As a reference in evaluating the performance of library service delivery, it is necessary to have Library Service Standards which must be implemented by all multi-unit and single-work area libraries within the National Research and Innovation Agency. To ensure that the library service standards are running well and giving satisfaction to the community, a community satisfaction survey (SKM) was conducted. The Community Satisfaction Survey (SKM) for library services was carried out as an effort to: 1) determine the level of service staff performance and service quality; 2) obtain an overview of public opinion/perception of the quality of public services; and 3) obtaining input materials for evaluation and establishment of policies in order to improve the quality of public services in the future.Methodology. This SKM activity is carried out at the end of each month and is evaluated quarterly in 2022 by distributing the SKM questionnaire online to users. The results of the questionnaires collected were then processed into community satisfaction index values (IKM).Results and Discussion. The evaluation results obtained the IKM value with very good criteria, namely achieving a value of 3.71 with a conversion value of 92.8. This value indicates that respondents are satisfied with the library services provided by the RMPI-BRIN Library.Conclusion. The IKM score category 92.8 (category A) indicates that library services have been carried out well and must be maintained.